Identifying Factors Affecting the Pharmaceutical Supply Chain Management in Iran - Esmaeillou, Yaser; Masoudi Asl, Iravan; Tabibi, Seyed Jamalleddin; Cheraghali, Abdol majid (Galen Medical Journal, 2017)
Background: This study has been conducted with the aim to identify factors affecting the management of pharmaceutical supply chain in Iran. Materials and Methods: This study was of a combined(quantityâ€“quality)type. The assessment tool was a Likert scale-based five-option questionnaire. Content validity assessment was obtained at 0.89 according to the CVR, and construct validity was at 0.971 using factor analysis.KMO statistics was very high and indicative of a correlation of scale items.In terms of reliability of assessment in reÂsearcher-made tools, the selected items were analysed, and the results obtained showed that the applied scales enjoyed significant reliability.The sample for the survey was100experts in the pharmaceutical system of the countryâ€™s Food and Drug Administration, pharmaceutical companies, technical officer of pharmacies and the ministry of health and medical education. They were selected by purposive stratified non-random sampling and snowball methods. The data was analysed by exploratory factor analysis using SPSS and LISREL. Results: The reÂsults of the current study indicated a pattern with significant and direct relationship between independent and dependent variables of medicine supply chain management. The most imÂportant indicators of medicine supply chain management in order of priority were distribuÂtion management with impact factor, IT management, pharmaceutical structure, pharmaceutiÂcal structure programming, coordination, enterprise resource planning, logistics management, knowledge management, financial management, globalization, customer relationship manageÂment, and medical insurance system. Conclusions: According to the patterning indexes, it can be mentioned that the representative model has had a good fit, and a desirable compliance between a structural model with experimental data and expert opinion has been provided.[GMJ.2017;6(4):346-55] DOI: 10.22086/gmj.v6i4.869